Health at school: the approach of educators about the ectoparasitoses in two public schools of the municipality of Murici, Alagoas/Saúde na Escola: a abordagem de educadores sobre as ectoparasitoses em duas escolas públicas do município de Murici, Alagoas - João Paulo Martins de Araújo; José Rodrigo da Silva Ferreira; Thiago José Matos Rocha; Claudia Maria Lins Calheiros (Universidade Estadual de Alagoas, 2020)
The parasites that inhabit the human integumentary system are called ectoparasites, being responsible for causing ectoparasitárias diseases. These are usually recurring diseases in children and adolescents of school age. In order to determine an initial diagnosis about the problems in our environment, this study developed through the vision of educators (teachers and administrators) of two elementary municipal schools of Murici-AL, and order check, some Myths linked to the basic concepts, as well as the song is worked in the school. For this we used a data collection instrument, represented by a questionnaire to teachers, containing objective questions about various aspects of the various ectoparasitoses. As direct benefits, was handed a pamphlet of educational awareness about the major ectoparasites with basic information about the life cycle, transmission and treatment. It was found that 31% of educators consider the ectoparasitoses as a public health problem, and 97% say be the pediculosis and scabies the bestknown ectoparasitoses. 70, 60 and 50% of educators, respectively, were Larva Migrans Cutanea, Tungiase and Myiasis. With respect to pediculosis, 52% make the diagnosis and communicated to the responsible. As for the myths of pediculosis, 14% think the transmission involves animals; 79% think that the school is not a source of infestation; 86% think the transmission is related exclusively to the socioeconomic factor and 21% agree that the lice jump or fly. We identified the existence of many questions and myths about the thematic work, being imperious need of addressing the topics of health education, as calls for the national curricular parameters (PCNs), so that students to achieve better quality of life and can enjoy a physical, mental and social development healthy for a full educational performance.